Arthropods - San Luis Video Publishing (Los Osos, California : San Luis Video Publishing, 2004)
Discussion of the largest group of animals, those with jointed legs: the phylum arthropods. The five classes explored are: insects, arachnids, centipedes, millipedes, and crustaceans. Arachnids shown include: spiders, mites, ticks, scorpions, whip scorpions, daddy longleg, and sun scorpions. The life histories of centipedes and millipedes are discussed. Characterisitcs of each of these classes are illustrated
Vol.1 - Artropods - Insect families and identification ; Vol.2 Insect orders, classification and identification - insect structure, function and metamorphosis
Title from first title in vol. 1 of dvd
DVD Format
Keywords: Entomology; Arthropods; Insects